A New Dynamic Intelligent Model to Determine Reliability and Trust of Online Banking by Using Fuzzy C-Mean - Ali Mohammad Rezaiee; Abbas Karimi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The main purpose of the present study presents a new model of smart dynamically determine the validity and reliability survey of Internet users bank is using Fuzzy C-Mean model. In other words, the aim of this study is to provide a smart system to determine the behavior of Internet users bank is confidence, so that we can fit the points by the customer, providing banking services to defined limits. In terms of method, a descriptive and exploratory data mining is in use. The method of research was descriptive survey and the use of data mining, exploration. The aim of this study is applied. The survey of methods for qualitative and quantitative data. Since the data of the Agricultural Bank documents (bills of transfer, transfer funds transfers, the number of IT users, foundations, etc.) were collected and interviews with experts in the field of electronic banking Agricultural Bank, Agricultural Bank branch target population for were randomly selected. The results showed that the diagnostic accuracy provided structure to determine the acceptable level of confidence in Internet banking is user behavior.